2‐Thiopheneformamidinium‐Based 2D Ruddlesden–Popper Perovskite Solar Cells with Efficiency of 16.72% and Negligible Hysteresis. Issue 28 (5th June 2020) - Dong, Yixin; Lu, Di; Xu, Zhiyuan; Lai, Hongtao; Liu, Yongsheng
Abstract: Formamidinium (FA)‐based 3D perovskite solar cells (PSCs) have been widely studied and they show reduced bandgap, enhanced stability, and improved efficiency compared to MAPbI3 ‐based devices. Nevertheless, the FA‐based spacers have rarely been studied for 2D Ruddlesden–Popper (RP) perovskites, which have drawn wide attention due to their enormous potential for fabricating efficient and stable photovoltaic devices. Here, for the first time, FA‐based derivative, 2‐thiopheneformamidinium (ThFA), is successfully synthesized and employed as an organic spacer for 2D RP PSCs. A precursor organic salts‐assisted crystal growth technique is further developed to prepare high quality 2D (ThFA)2 (MA) n −1 Pb n I3 n +1 (nominal n = 3) perovskite films, which shows preferential vertical growth orientations, high charge carrier mobilities, and reduced trap density. As a result, the 2D RP PSCs with an inverted planar p‐i‐n structure exhibit a dramatically improved power conversion efficiency (PCE) from 7.23% to 16.72% with negligible hysteresis, which is among the highest PCE in 2D RP PSCs with low nominal n ‐value of 3. Importantly, the optimized 2D PSCs exhibit a dramatically improved stability with less than 1% degradation after storage in N2 for 3000 h without encapsulation. These findings provide an effective strategy for developing FA‐based organic spacers toward highly efficient and stable 2D PSCs. Abstract : A formamidinium derivative, 2‐thiopheneformamidinium (ThFA), is successfully developed and used as a spacer in 2D RP perovskite (ThFA)2 MA n −1 Pb n I3 n +1 (nominal n = 3). A precursor organic salts‐assisted crystal growth technique is further developed to prepare high‐quality 2D RP perovskite films, resulting in a high power conversion efficiency of 16.72% with negligible hysteresis and improved stability.